Archaeal amoA gene diversity points to distinct biogeography of ammonia-oxidizing Crenarchaeota in the ocean - Sintes, Eva (Blackwell Publishing Ltd, 2013)
Mesophilic ammonia-oxidizing Archaea (AOA) are abundant in a diverse range of marine environments, including the deep ocean, as revealed by the quantification of the archaeal amoA gene encoding the alpha-subunit of the ammonia monooxygenase. Using two different amoA primer sets, two distinct ecotypes of marine Crenarchaeota Group I (MCGI) were detected in the waters of the tropical Atlantic and the coastal Arctic. The HAC-AOA ecotype (high ammonia concentration AOA) was ≍ 8000 times and 15 times more abundant in the coastal Arctic and the top 300 m layer of the open equatorial Atlantic, respectively, than the LAC-AOA (low ammonia concentration AOA) ecotype. In contrast, the LAC-AOA ecotype dominated the lower meso- and bathypelagic waters of the tropical Atlantic (≍ 50 times more abundant than the HAC-AOA) where ammonia concentrations are well below the detection limit using conventional spectrophotometric or fluorometric methods. Cluster analysis of the sequences from the clone libraries obtained by the two amoA primer sets revealed two phylogenetically distinct clusters. Taken together, our results suggest the presence of two ecotypes of archaeal ammonia oxidizers corresponding to the medium (1.24 µM on average in the coastal Arctic) and low ammonia concentration (< 0.01 µM) in the shallow and the deep waters respectively.